SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN PENJURUSAN DI SMA YADIKA BANGIL DENGAN MENGGUNAKAN METODE AHP(STUDI KASUS PADA SMA YADIKA BANGIL) - Erri Wahyu Puspitarini, Dewi Kartika Yusti Hidayati (SPIRIT, 2018)
In the world of education especially at the high school level majors is very important because of the expected student majors - students may know the talents and interests owned by them so as to be equipped to continue in higher education anymore. During these majors are usually only seen on one or two factors at the example just seen from just rapo and psychological tests to determine even the majors only be seen from the rapot alone. Majors should also have to consider the wishes of students and also incorporates the two above factors so as to produce a more informed decision falid and purposeful.Therefore, it is needed a Decision Support System majors to facilitate rapid decision-making in a precise and accurateKeywords : Decision Support System, Analytic Hierarchy Process Method,PHP, MY sql, Sistem Penjurusan.